Sustentabilidade na implantação de projetos de obras públicas - Pisani, Angela Paulina Grandeaux (2021)
In the context of sustainability in public constructions, two aspects can be highlighted: the civil construction has high economic impact in Brazil, while local governments are major buyers and hirers of such services. Local governments are also change inductors regarding patterns of production and consumption, that being on the role of policy-makers, regulators or large-scale consumers. Therefore, government’s actions that contribute to improve the efficiency of productive systems and processes of inputs management have great impact for its scale and reach. It is inside this realm that this research is inserted, on account of applying criteria of sustainability in public constructions’ projects. In a particular way, the intention is to study the municipality of Santa Maria, where the public bidding of public constructions is currently under the Municipal Executive Decree nº 007, which regulates the article 15 of the law nº 8.666 in the municipal scale, that does not respond to the national concepts of sustainability under the article 3º of the same law. Hence, the scope of this research is to develop a method for the application of sustainability criteria in architectural and civil engineering projects of municipal public constructions. Albeit, without this method inflicting the existing regulations on both federal and municipal scales. The objective of this research is to develop, consolidate and evaluate a method for the insertion of sustainable practices in public constructions’ projects. In order to reach this goal, the Design Science Research (DSR) will be used as the research method. Opposed to the majority of approaches in academic research, that look for an accumulation of theoretical knowledge, the DSR has as its main purpose the comprehension and resolution of problems. This methodology is already consolidated in both national and international scope. The choice of methodology is justified by the development of a tool to solve a real problem. The tool generated by this research will constitute an integrated method to incorporate sustainability criteria in public constructions’ projects.